(untitled) (International Journal of Physiotherapy, 2017)
Background: Aging is a physiologic process that affects all of our body systems. It is characterized by a physiological decline in bodily functions. Physical fitness helps to maintain a good quality of life. Thus we need to study the effect of physical activity on one’s physical fitness. The main aim of our study was to compare physical fitness in community-dwelling elderly and institutionalized elderly using Senior Fitness Test (SFT). This test assessed strength, flexibility, balance and endurance. These components are frequently used in one’s daily activities and thus helpful to evaluate physical fitness. Since there is an increase in the number of elders becoming institutionalized, it is imperative to understand if there is a difference in demands on their bodily systems which will affect their fitness parameters, hence this study was undertaken. Methods: Two groups were selected (n=40) which included 20 individuals from the community and 20 from an institution. Their fitness level was evaluated using Senior Fitness Test (SFT) which had six components to assess upper body strength and upper body flexibility, lower body strength and lower body flexibility, 8 feet test, 6-minute walk test. Result: Comparison of SFT components was made by using unpaired t-test and Mann-Whitney test. Analysis of this study revealed significant difference in lower body strength (p value=0.0028), 8 feet test (p value=0.0205) and 6-minute walk test (p value=<0.0001) which was better in community-dwelling elderly than institutionalized elderly. Also, upper body flexibility (p-value = 0.4477) and lower body flexibility (p-value =0.0766) were better in community-dwelling elderly though was not statistically significant. Conclusion: The current study suggests that community-dwelling elderly have better lower body strength, dynamic balance and aerobic endurance in comparison to institutionalized elderly of the same age group. Thus, it can be said that staying in institutions, in a restricted environment with less amount of physical activity has a negative impact on one’s functional and physical independence.